Sistem Pendukung Keputusan Penentuan Wali Kelas Berdasarkan Prestasi Guru Dengan Metode Analytical Hierarchy Process (AHP) Berbasis Web - Aminuddin, Fattachul Huda; Riyanda, Afif Rahman; Djauhari, Teuku (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Decision Support System (DSS) is a procedure-based model for processing data and assisting management in making decisions. Decision Support System (DSS) is a problem solving program and provides a solution to a decision in both structured and unstructured situations. Currently in the homeroom at SMA Ferdy Ferry Putra Jambi, it is still done subjectively by the principal. The assessment carried out by the principal is only based on the internal closeness factor between the teacher and the principal. Some possibilities for homeroom teachers are also based on age and years of service at school, causing injustice among teachers. The purpose of this study is to assist the school in determining homeroom teachers based on the achievements and services of teachers in educating students. The research method used is the Analytical Hierarchy Process (AHP) method. Research in making this application is carried out using the waterfall model with 6 stages, namely needs analysis, design or design, coding, testing, implementation, and maintenance. Making this application program was developed with the PHP programming language and the database used is MySQL. With this system, it can help the school in determining the ranking of teachers based on the value of services that will be selected as homeroom teachers